Cells : a laboratory manual - Spector, David L; Goldman, Robert D; Leinwand, Leslie A (Cold Spring Harbor Laboratory Press, 1998)
Having identified a gene product, how do you determine what it does? The answer lies in Cells, a new manual designed to do for studies of cell biology what Cold Spring Harbor\'s Molecular Cloning has done for molecular biology. Sets the standard for techniques of proven bench reliability needed by all biomedical scientists studying cellular structure and function. Delivers consistent, precisely crafted step-by-step protocols in an accessible format, with essential background details and in-depth advice on pitfalls and problem solving. Created by three distinguished cell biologist/educators, from the contributions of over 180 leading cell biologists. Complete with more than 300 expertly selected and superbly reproduced illustrations, over 70 in color. Volume 1: Culture and Biochemical Analysis of Cells Volume 2: Light Microscopy and Cell Structure Volume 3: Subcellular Localization of Genes and Their Products
Keywords: biologie buňky; Cell Biology; chemie, klinická chemie; cytologie, klinická cytologie